Carbon materials derived from polymerization of bio-oil as a catalyst for the reduction of nitrobenzene. Issue 11 (18th May 2021) - Xu, Qing; Gao, Guoming; Tian, Hongli; Gao, Zhiran; Zhang, Shu; Xu, Leilei; Hu, Xun
Abstract : The bio-oil based carbon material modified by KOH activation and O, N doping is a promising non-metallic catalyst for nitrobenzene reduction with hydrazine hydrate as a reducing agent. Abstract : Bio-oil is a condensable liquid obtained from pyrolysis of biomass, which is the feedstock not only for the production of biofuels, but also for the production of functional carbon materials. In this study, carbon materials derived from the polymerization of bio-oil and furfural were treated with varied methods and were used as catalysts for the reduction of nitrobenzene to aniline with hydrazine hydrate as a reductant. The results showed that the oxidation of carbon materials with HNO3 formed more CO and CN functionalities, and created some defects, while the doping with urea led to the elimination of the carbonyl functionalities. The presence of N species in the carbon materials changed the electronic state of the carbon atom and induced the skeleton expansion of the graphite structure in the carbon materials, creating remarkably more defect sites than from the oxidation with HNO3 . These defective structures were essential for endowing the carbon materials with superior catalytic activity and stability for the selective reduction of nitrobenzene to aniline.